ANÁLISE ESPACIAL DA OCORRÊNCIA DE LEISHMANIOSE VISCERAL NO BRASIL. - FONTOURA, Iolonda Graepp (2018)
Visceral Human Leishmaniasis (LVH) is a disease of great epidemiological significance, becoming a public health problem with high morbidity and mortality rates; and in regions where the geographical overlap of LVH and human immunodeficiency virus (HIV) occurs, these rates are even higher. The objective of this study was to identify spatial patterns of the distribution of visceral leishmaniasis in Brazil between the years 2001 and 2015. The methodology used was an ecological and exploratory study, using geoprocessing tools to elaborate thematic maps, constructed by the software TerraView 4.2.2 , with secondary data obtained from the Brazilian Institute of Geography and Statistics (IBGE) and the Department of Informatics of the Unified Health System (DATASUS). This software allowed us to obtain the values ​​of global Moran - I and local Moran - LISA. A total of 53,994 cases of visceral leishmaniasis were reported in the study period between 2001 and 2015, with an average annual rate (TMA 2.59 / 100,000 inhabitants (hab.)); male, 33,502 (62%, TMA 2.43 / 100,000 people); higher incidence among indigenous people (TMA 2.91 / 100,000 inhabitants); prevalence between 1 and 4 years (30%); greater incidence in <1 year (TMA 3.76 / 100,000 inhabitants); 3,589 deaths (rate 0.12 / 100,000 inhabitants); higher proportion in the Northeast region, 29,968 (56%); incidence in the Northern region (TMA 7.04 / 100,000 inhabitants). Maranhão was the prevalent, with 8,194 (15%) of the reported cases; highest index in the state of Tocantins (TMA 21.65 / 100,000 inhabitants); 2,221 cases of LVH / HIV coinfection in the study period between 2007 and 2015 (TMA 0.13 / 100,000 inhabitants), in 204 Brazilian municipalities (4%). The main epidemiological characteristics of the cases of LVH / HIV coinfection were: mainly men (77%, TMA 0.20 / 100,000 inhabitants); prevalent in the age group between 20 and 39 years old (51%), with higher TMA between 40 and 59 years old (TMA 0.20 / 100,000 inhabitants); is concentrated mainly in the Northeast region (51%), with the highest TMA in the Central West region (TMA 0.26 / 100,000 inhabitants); high concentration of cases in Minas Gerais (17%), with the highest TMA in the state of Mato Grosso do Sul (TMA 1.17 / 100,000 inhabitants). The overall Moran index was 0.46 (p <0.01), which indicated similarity among municipalities with significant spatial autocorrelation. It was possible to observe the presence of similar clusters between the neighboring municipalities in the thematic maps of LVH, Visceral Canine Leishmaniasis (LVC), LVH / HIV, HIV, trash, without sewage network and lower human development index (HDI). Moran Map maps for the Northeast region, part of the Center-West region, part of the North region and LISA Map showed statistically significant clusters (p <0.001). It is concluded that the geoprocessing technique allowed the detection and analysis of the agglomerates of LVH rates with the proposed variables, as well as the sites with higher and lower intervention needs. It was possible to observe a gradual decrease in the LVH TMA, maintenance of mortality rates and a slight decrease in the TMA of new cases, but a significant increase in the number of cases of LVH / HIV coinfection.